Parental Impact of Cultural Values on the Uptake of Human Papillomavirus (HPV) Vaccination by Their Daughters: A Protocol of Qualitative Meta-synthesis - Noor Shuhada, Salleh; Lim, Khatijah Abdullah * (Faculty of Medicine and Health Sciences, 2024)
The aim of this systematic review is to explore how parents’ perspectives on the human papillomavirus (HPV) vaccination are influenced by their cultural values, specifically with regard to their daughters. Adolescent girls are generally the primary targets for HPV vaccination and, in the majority of countries, parents/legal guardians have overall authority on this issue. However, it appears that cultural values could prove a powerful indicator in the parental choices that affect the uptake of HPV vaccination, which therefore needs to be carefully considered. Thus, exploring parents’ views is critical in improving HPV vaccination coverage. Methods: A systematic literature search will be conducted using CINAHL, PsycINFO, EMBASE, PubMed and Science Direct to identify eligible studies published in the English language. Two reviewers will select the studies independently and the quality of the studies will be evaluated using the Critical Appraisal Skills Program (CASP) checklists. Thematic synthesis methods will be used to report themes specific to cultural values. Discussion: It is predicted that the results of the proposed review will be beneficial to identify and understand the culturally-related facilitators and barriers to the HPV vaccination of young women, as they are central to the HPV vaccination programme. Once concerns raised by parents are understood more fully, relevant interventions can be developed to address these concerns. This information is also crucial to the development of strategies to optimise HPV vaccine coverage among this population group by policy makers. Malaysian Journal of Medicine and Health Sciences (2024) 20(2): 379-384. doi:10.47836/mjmhs.20.2.48